Peran Justice Collaborator Tindak Pidana Korupsi Terhadap Penegakan Hukum - Sari, Ayu Wahyuning (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In the Indonesian legal system, justice collaborators, or cooperating witnesses, play a crucial role in combating organized crime, particularly corruption, which is categorized as an extraordinary crime and a white-collar crime. Therefore, strategies for law enforcement against corruption require special approaches, one of which is collaborating with justice collaborators or offenders who cooperate with law enforcement authorities. A justice collaborator is defined as a perpetrator of a criminal act who is not the main offender. Their strategic role includes providing significant information regarding the chronology and modus operandi of the crime, revealing other parties with greater involvement, and assisting in the recovery of state assets. This study aims to analyze the strategic role of justice collaborators in uncovering corruption cases and their contribution to law enforcement. The research method employed is normative juridical, using a statutory approach relevant to the legal issues examined. The findings show that the role of justice collaborators can expose corruption networks that are otherwise difficult to prove, as the perpetrators are individuals holding positions of power and authority. Substantial cooperation with justice collaborators is therefore intended to ensure quality law enforcement, carried out by prioritizing the principles of swift and simple justice.